Educational Engineering in the Face of Extremism: international and political journal - Ali, Assistant Lecturer: Ahmed Faisal (The International and Political Journal, 2024)
Post-conflict societies face many challenges, most notably extremist ideological frameworks, which in turn calls for the need to find effective strategies to dispel these frameworks. Education is one of the most effective strategies to confront extremist frameworks and ideas, and to replace a value system that believes in accepting and recognizing the other, in a way that enhances societal security and stability. The effectiveness of education lies in confronting extremism by engineering it and then rebuilding it according to dynamic structures characterized by flexibility and the ability to respond to challenges that may hinder the path of combating extremism and its ideological frameworks, in addition to consolidating joint work between educational institutions on the one hand, and security institutions and civil society organizations on the other hand.